THE EFFECT OF INVENTORY TURNOVER AND DEBT-TO-EQUITY RATIO ON PROFITABILITY WITH INFLATION AS MODERATION - Salim, Wijaya; Santoso, Wiliam; Widianingsih, Luky Patricia (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2025)
This study investigates the effect of inventory turnover (ITO) and debt-to-equity ratio (DER) on profitability, specifically return on assets (ROA), with inflation acting as a moderating variable. Using secondary data from the financial statements of 17 IDX-listed retail firms from 2021 to 2023, the research employs multiple linear regression and MRA. The findings reveal that ITO and DER have no significant direct effect on ROA, highlighting the complexity of their role in profitability. Interestingly, while inflation does not moderate the relationship between ITO and ROA, it does weaken the negative effect of DER on ROA under high inflation conditions. This suggests that inflation may influence profitability indirectly through the company’s ability to adjust its financial strategies, such as pricing and debt management, rather than directly affecting operational efficiency or capital structure. This research contributes to the literature by addressing the limited research on the moderating role of inflation in the relationship between financial ratios and profitability, particularly in the retail sector. It extends the application of agency theory in understanding how managerial decisions related to inventory and debt are influenced by external macroeconomic pressures. The results emphasize the need for a more comprehensive understanding of profitability determinants, suggesting that both internal management strategies and external factors must be considered to better navigate economic uncertainties.